Acute rheumatic fever associated with tenosynovitis and a unique cytokine profile. Issue 1 (2nd January 2018) - Wakiguchi, Hiroyuki; Okazaki, Fumiko; Suzuki, Yasuo; Ichimura, Takuya; Wakabayashi-Takahara, Midori; Terachi, Shin-Ichi; Ouchi, Kazunobu; Hasegawa, Shunji
Abstract: Acute rheumatic fever (ARF), caused by group A β-hemolytic streptococcus infection, is characterized by inflammation affecting several organs. There are few reports on magnetic resonance imaging (MRI) findings in patients with ARF. An 8-year-old Japanese boy presented with a prolonged fever of unknown cause and swelling of his right hand. MRI of his hand revealed tenosynovitis. Migratory arthritis and erythema marginatum appeared following the hand swelling. We diagnosed him as having ARF based on the clinical course and serological testing for group A β-hemolytic streptococcus. His serum interleukin-18 levels were lower than those typically seen in cases of systemic juvenile idiopathic arthritis (sJIA). After treatment with naproxen, his symptoms improved immediately. In conclusion, MRI findings of tenosynovitis may be useful for the diagnosis of not only sJIA but also ARF in patients presenting with a fever of unknown origin. Subsequently, the diagnosis of ARF can be confirmed with specific serological tests. Serum interleukin-18 levels may be helpful in the differential diagnosis of ARF and sJIA. Although ARF is rare in developed countries, including Japan, early diagnosis and appropriate treatment are important to prevent rheumatic heart disease.